Penerimaan Diri Remeja Obesitas Tingkat II Di Desa Semen - Ari Tri Irawan; Akhmad Hasan Saleh; Nisa Fitriani (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2025)
Adolescents who are obese often experience verbal and nonverbal disturbances from their environment. In this context, self-acceptance plays a role so that individuals know their strengths and weaknesses and understand how to behave with the environment. This study aims to determine the description of self-acceptance of obese adolescents and the factors that influence self-acceptance of obese adolescents in Semen Village. This study uses a qualitative research method with a descriptive approach. The location of this study is in Semen Village. The primary data source in this study was 4 obese adolescents, 2 male and 2 female. Data collection techniques used interview, observation, and documentation methods. Data validity checking was carried out using the triangulation method or technique, while data analysis techniques were carried out by reducing data, presenting data, and drawing conclusions, according to Lexy J. Moleong. The results of the study showed that self-acceptance of obese adolescents in Semen Village was characterized by being able to accept themselves, be confident in themselves, understand their limitations, know their potential, and admit their weaknesses without blaming themselves. The four informants had not been able to show a sense of acceptance of themselves towards their physical condition of obesity. Factors that influence self-acceptance of the four informants include having an understanding of oneself, having realistic expectations, having no obstacles in the environment, having pleasant attitudes of community members, having no severe emotional disturbances, having the influence of success, identifying with people who have good adjustments, having a broad self-perspective, having good parenting in childhood, and having a stable self-concept Keywords: Self-Acceptance, Adolescents, Obesity